Solve x^3+2*x^2-5*x-6=0

First find a root of the function: f(x)=x^3+2x^2-5x-6 f(2)=(2)^3+2*(2)^2-5*(2)-6 =0. Therefore, (x-2)(x^2+Ax+3)=0 where A is an unkown constant. Compare x^2 coeffecients: A-2=2, A=4. So (x-2)(x^2+4x+3)=0. Then factorise the quadratic to get (x-2)(x+3)(x+1)=0. Therefore x=2 or x=-3 or x=-1

Answered by Maths tutor

2284 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Differentiate the following, y=(2x-4)^3


Explain briefly the Normal Distribution


Use integration by parts to find ∫x e^(x)


A cricket player is capable of throwing a ball at velocity v. Neglecting air resistance, what angle from the horizontal should they throw at to achieve maximum distance before contact with the ground? How far is that distance?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo

© MyTutorWeb Ltd 2013–2025

Terms & Conditions|Privacy Policy
Cookie Preferences